Health Care Needs According to the Life-Cycle of Community Residents (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study analyzes health care needs by life cycle and provides basic data for developing health care programs accordingly.Methods/Statistical analysis: Tools for measuring the health care needs of the subjects were revised and supplemented by the tools of the Community Health Survey. Data was collected through a questionnaire from August 1 to August 21, 2018. Although 897 questionnaires were collected, 843 questionnaires were used for data analysis, except for 54 which were not clear or missing. The collected data were analyzed with the SPSS 18.0 program.Findings: The analysis of health care needs by life cycle was the highest in adolescents with 3.41 out of 4.0, followed by 3.40 in childhood, 3.39 in elderly, 3.35 in adulthood, and 3.31 in pregnancy. The difference in the health care needs by life cycle according to the general characteristics is as follows: in the difference analysis of health needs by gender and life cycle, there was a statistically significant difference in adolescents (t=-2.770, p=.006) and adulthood (t=-1.970, p=.049). There was also a statistically significant difference in health needs in adolescence (F=2.225, p=.039) and adulthood (F=2.449, p=.024). The difference between marital status and health demand was statistically significant in adolescence (F=4.570, p=.001) and adulthood (F=3.715, p=.005).Improvements/Applications: Therefore, in order to improve the health potential of the residents, it is necessary to develop a health care program according to the life cycle.